Identification of stable housekeeping genes for induced pluripotent stem cells and -derived endothelial cells for drug testing - Sheena L. M. Ong; Hans J. Baelde; David G. P. van IJzendoorn; Judith V. M. G. Bovée; Karoly Szuhai (Scientific Reports)
Abstract There are no validated housekeeping genes in induced pluripotent stem cells (iPSC) and derived endothelial iPSC (iPSC-EC). Thus a comparison of gene expression levels is less reliable, especially during drug treatments. Here, we utilized transcriptome sequencing data of iPSC and iPSC-EC with or without CRISPR-Cas9 induced translocation to identify a panel of 15 candidate housekeeping genes. For comparison, five commonly used housekeeping genes (B2M, GAPDH, GUSB, HMBS, and HPRT1) were included in the study. The panel of 20 candidate genes were investigated for their stability as reference genes. This panel was analyzed and ranked based on stability using five algorithms, delta-Ct, bestkeeper, geNorm, Normfinder, and Reffinder. Based on the comprehensive ranking of Reffinder, the stability of the top two genes—RPL36AL and TMBIM6, and the bottom two genes—UBA1 and B2M, were further studied in iPSC-EC with and without genetic manipulation, and after treatment with telatinib. Using quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR), it was shown that gene expression of the top two housekeeping genes, RPL36AL and TMBIM6, remained stable during drug treatment. We identified a panel of housekeeping genes that could be utilized in various conditions using iPSC and iPSC-derived endothelial cells as well as genetically modified iPSC for drug treatment.